Advances in ultrahigh-energy resolution EELS: phonons, infrared plasmons and strongly coupled modes. (18th February 2022) - Lagos, Maureen J; Bicket, Isobel C; Mousavi M., S Shayan; Botton, Gianluigi A
Abstract: Nowadays, sub-50 meV atom-wide electron probes are routinely produced for electron energy loss spectroscopy in transmission electron microscopes due to monochromator technology advances. We review how gradual improvements in energy resolution enabled the study of very low-energy excitations such as lattice phonons, molecular vibrations, infrared plasmons and strongly coupled hybrid modes in nanomaterials. Starting with the theoretical framework needed to treat inelastic electron scattering from phonons in solids, we illustrate contributions in detecting optical surface phonons in photonic structures. We discuss phonon mapping capabilities in real and reciprocal space, and the localized phonon response near nano-/atomic-scale structural features. We also survey the progress of aloof spectroscopy in studying vibrations in organic materials and applications in measuring local temperature and photonic density of states in single nanostructures using phonon scattering. We then turn towards studies on infrared plasmons in metals and semiconductors. Spectroscopy analyses now extend towards probing extremely complex broadband platforms, the effects of defects and nanogaps, and some far-reaching investigations towards uncovering plasmon lifetime and 3D photonic density of states. In doped semiconductors, we review research on the use of the electron probe to correlate local doping concentration and atomic-scale defects with the plasmonic response. Finally, we discuss advances in studying strong coupling phenomena in plasmon–exciton and plasmon–phonon systems. Overall, the wealth of information gained extends our knowledge about nanomaterial properties and elementary excitations, illustrating the powerful capabilities of high-energy resolution scanning transmission electron microscopy–electron energy loss spectrometry.